ANALYSIS OF MAN INSAN CENDEKIA PASER STUDENTS' UNDERSTANDING OF THE ERA OF GLOBAL COMPLEXITY - Kirana, Ratih; Zamroni, Zamroni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyze the understanding of MAN Insan Cendekia Paser students regarding the era of global complexity, characterized by rapid changes in technology, social dynamics, economy, and culture. Using a descriptive qualitative approach, data were collected through observations, interviews, and questionnaires completed by students and teachers. The results show that most students have a good understanding of the concept of the global complexity era, including the importance of 21st-century skills such as critical thinking, communication, and collaboration. Key factors supporting students' understanding include the integration of technology into learning and the global competency-based programs organized by the school. However, challenges such as limited access to relevant information and difficulties in technology adaptation remain. This study recommends improving global literacy, introducing more cross-cultural educational programs, and utilizing more effective technology-based media to strengthen students' readiness for the era of global complexity